Improving medical students' attitude toward patients with substance use problems through addiction medicine education. Issue 1 (1st December 2022) - Ayu, Astri Parawita; van der Ven, Margot; Suryani, Eva; Puspadewi, Natalia; Joewana, Satya; Rukmini, Elisabeth; de Jong, Cor; Schellekens, Arnt
Abstract: Background: Patients with addiction often encounter negative attitudes from health care professionals, including medical doctors. Addiction medicine training might improve medical students' attitudes toward patients with addiction problems and change the way they think about addiction. We evaluated the effect of comprehensive addiction medicine training on students' attitudes and illness perceptions and explored which perceptions are most relevant for attitude development. Methods : In a quasi-experimental non-randomized study, fourth-year students ( n = 296) participated in either addiction medicine training (intervention) or one of three other blocks (control). We used the Medical Condition Regards Scale to measure attitudes and the Illness Perception Questionnaire Addiction version for perceptions. We analyzed the effect of the intervention using repeated measures MANOVA. The contribution of illness perception to attitude was explored in the intervention group using linear regression analysis. Results : Addiction medicine training improved students' attitudes toward patients with addiction, compared to the control group. After the training, students expressed a less demoralized perception, a stronger perception of a coherent understanding of addiction, addiction as a cyclical condition, and attributed addiction more to psychological factors, compared to the control group. In the intervention group, attitude and emotional representation before training and illness coherence after the training were associated with attitude after the training. Conclusions : Addiction medicine training is effective in improving medical students' attitudes toward patients with addiction and changing their illness perceptions of addiction. The development of an understanding of addiction might be particularly relevant for attitude improvement. These findings underscore the relevance of addiction medicine training as part of medical curricula and argue for including aspects related to attitude development in the curriculum.